Investigation of the usage of zigzag transformers to reduce harmonics distortion in distribution systems - Gumilar, Langlang; Wicaksono, Ibram Adib; Afandi, Arif Nur; Samat, Ahmad Asri Abd; Sias, Quota Alief (National Research and Innovation Agency, 2023)
The increasing use of power electronics in various sectors leads to harmonic distortion in electric power systems, affecting power quality and equipment longevity. While harmonic filters have been used to address this issue, they are limited in effectiveness, particularly in reducing distortion across the entire distribution system. This study aims to reduce harmonic distortion using a zigzag transformer as a more comprehensive solution in mitigating harmonic distortion throughout the entire distribution system. In this research, the zigzag transformer was placed at point common coupling to reduce harmonic distortion in the distribution system as a whole. A zigzag transformer connection was configured by connecting either three windings of a single-phase transformer or one winding of a three-phase transformer. Based on the results of this research, the total harmonic distortion (THD) value has decreased from 25.26 % to 2.48 % following the implementation of the zigzag transformer. This substantial decrease in THD concludes the zigzag transformer's effectiveness as a solution for improving power quality in electrical distribution systems.